CHARACTERISATION OF THE PARASITE LOAD OF RIVER BISTRITA TRIBUTARIES, IN DORNELOR BASIN, ROMANIA - Ionela VOLOSENIUC; Kálmán IMRE; Liviu MIRON (Journal of Applied Life Sciences and Environment)
Dornelor Basin is characterised by numerous high quality water sources, which is proven by the fact that the main mineral waters on the Romanian market come from this area. The study aimed to provide data on the occurrence and human infective potential of Giardia and Cryptosporidium, as the most important water-borne parasites, from Bistrița river tributaries of Dornelor basin, North-Eastern Romania. Water samples were collected from 10 tributaries of the Bistrita river, from the level of sampling stations set upstream and downstream from the anthropic communities. The harvested water samples were further processed using non-molecular methods in order to isolate (oo)cysts. Subsequently, the isolated Cryptosporidium and Giardia (oo)ccyst were molecularly characterized through PCR and genomic sequencing, which led to the identification of Giardia in order to identify them at species level. The outcomes revealed the fact that the waters of the emissaries under study have a low parasite load and that, upstream from the human settlements, the water is highly pure when related to the protozoa under study. The increased load of Giardia spp. and Cryptosporidium spp. corresponded to important animal husbandry activity. The obtained results underline a potential public health risk.